Digitalisasi dan Ekonomi Kreator: Analisis Peran Fujiiian Dalam Membangun Pertumbuhan Ekonomi Lewat Live Tiktok - Arby Pratama Haraha; Nazwa Amelia; Yuanita Dyah Aprilian; Kanaya Rianjani; Nakeisha Zahwa Shaqvilla (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
Digitalization has opened up new opportunities in the development of the creator economy, especially through live streaming platforms such as TikTok. This study aims to analyze the role of Fujiiian in driving economic growth through TikTok live activities. The research method used is descriptive qualitative with data collection through digital observation, interviews, and literature studies related to the creator economy and digitalization. The results of the study show that Fujiiian has succeeded in utilizing TikTok's live feature to build an active and engaged creator community, increase interaction with the audience, and optimize the monetization of creative content. This success is reflected in the increase in the number of followers, high engagement, and significant contributions to the growth of the creator economy on the platform. The strategies implemented include collaboration with other creators, the use of interactive content, and the use of relevant digital trends. This study concludes that digitalization through TikTok live is an effective means of strengthening the creator economy ecosystem, while encouraging inclusive and sustainable economic growth. It is recommended that Fujiiian continue to develop content innovation and interaction strategies to maintain and increase its economic impact.